2012
DOI: 10.1136/annrheumdis-2012-201706
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of psoriatic arthritis in patients with severe psoriasis with suboptimal performance of screening questionnaires

Abstract: 29% of Ps patients attending dermatology clinics had undiagnosed PsA. Psoriasis severity was associated with a new diagnosis of PsA. Poor sensitivities for the screening questionnaires were noted due to inadequate detection of patterns of arthritis other than polyarticular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
207
2
9

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 271 publications
(227 citation statements)
references
References 17 publications
9
207
2
9
Order By: Relevance
“…Though no absolute indicators have been identified to predict that a person with psoriasis may develop PsA, the presence of soluble biomarkers, for example, highly sensitive C‐reactive protein (hsCRP), osteoprotegerin (OPG), matrix metalloproteinase‐3 (MMP‐3) and the C‐propeptide of type II collagen to collagen fragment neoepitopes Col2‐3/4 long mono ratio or certain susceptibility genes (e.g. certain human leucocyte antigen alleles [HLA‐B and HLA‐C]) may confer susceptibility to PsA among patients with psoriasis 9, 10, 11, 12. Moreover, the predictive nature of clinical observations such as the severity of psoriasis (as measured by the Psoriasis Area Severity Index [PASI]), the severity of joint involvement and the presence of certain psoriasis features (e.g.…”
Section: Overcoming Barriers To the Early And Accurate Diagnosis Of Psamentioning
confidence: 99%
See 1 more Smart Citation
“…Though no absolute indicators have been identified to predict that a person with psoriasis may develop PsA, the presence of soluble biomarkers, for example, highly sensitive C‐reactive protein (hsCRP), osteoprotegerin (OPG), matrix metalloproteinase‐3 (MMP‐3) and the C‐propeptide of type II collagen to collagen fragment neoepitopes Col2‐3/4 long mono ratio or certain susceptibility genes (e.g. certain human leucocyte antigen alleles [HLA‐B and HLA‐C]) may confer susceptibility to PsA among patients with psoriasis 9, 10, 11, 12. Moreover, the predictive nature of clinical observations such as the severity of psoriasis (as measured by the Psoriasis Area Severity Index [PASI]), the severity of joint involvement and the presence of certain psoriasis features (e.g.…”
Section: Overcoming Barriers To the Early And Accurate Diagnosis Of Psamentioning
confidence: 99%
“…Moreover, the predictive nature of clinical observations such as the severity of psoriasis (as measured by the Psoriasis Area Severity Index [PASI]), the severity of joint involvement and the presence of certain psoriasis features (e.g. scalp lesions, nail disease and intergluteal/perianal psoriasis) with respect to the risk of developing PsA remains unclear 10, 13, 14, 15. Determining such absolute indicators for PsA remains complicated because of varying study designs (e.g.…”
Section: Overcoming Barriers To the Early And Accurate Diagnosis Of Psamentioning
confidence: 99%
“…Most have undergone validation, but until recently there has been little research directly comparing questionnaires with the aim of identifying one questionnaire that can be recommended for routine clinical use in the future. There have been 3 head-to-head comparisons that have shown conflicting results, but all have recognized problems in identifying PsA (2,7,8). In the CONTEST study, the questionnaires identified many cases who had musculoskeletal symptoms due to an alternative diagnosis, particularly osteoarthritis or degenerative disease, leading to poor specificity (7).…”
Section: Discussionmentioning
confidence: 99%
“…Data from 2 comparative independent head-to-head studies based in Dublin, Ireland and Utah were used to test the new proposed questionnaires (2,8). Both of these studies evaluated some patients with known PsA and some with psoriasis and no known diagnosis of inflammatory arthritis.…”
Section: Development Cohort (Contest)mentioning
confidence: 99%
“…По данным американских и евро-пейских исследователей [20,21], на долю больных ПсА приходится около 30% всех больных ПС. В бра-зильской популяции [22] ПсА отмечен у 33% паци-ентов с ПС.…”
unclassified